Platelet Count Rose While D-Dimer Levels Dropped as Deaths and Thrombosis Declined—An Observational Study on Anticoagulation Shift in COVID-19 - Sjöström, Anna; Wersäll, Johanna Dehlsen; Warnqvist, Anna; Farm, Maria; Magnusson, Maria; Oldner, Anders; Ågren, Anna; Antovic, Jovan; Bruzelius, Maria (Thrombosis and Haemostasis, 2021)
Background High levels of D-dimer and low platelet counts are associated with poor outcome in coronavirus disease 2019 (COVID-19). As anticoagulation appeared to improve survival, hospital-wide recommendations regarding higher doses of anticoagulation were implemented on April 9, 2020.Objectives To investigate if trends in D-dimer levels and platelet counts were associated with death, thrombosis, and the shift in anticoagulation.Methods Retrospective cohort study of 429 patients with COVID-19 at Karolinska University Hospital. Information on D-dimer levels and platelet counts was obtained from laboratory databases and clinical data from medical records.Results Thirty-day mortality and thrombosis rates were 19% and 18%, respectively. Pulmonary embolism was common, 65/83 (78%). Increased D-dimer levels in the first week in hospital were significantly associated with death and thrombosis (odds ratio [OR]: 6.06; 95% confidence interval [CL]: 2.10–17.5 and 3.11; 95% CI: 1.20–8.10, respectively). If platelet count increased more than 35 × 109/L per day, the mortality and thrombotic risk decreased (OR: 0.16; 95% CI: 0.06–0.41, and OR: 0.36; 95% CI: 0.17–0.80). After implementation of updated hospital-wide recommendations, the daily mean significantly decreased regarding D-dimer levels while platelet counts rose; −1.93; 95% CI: −1.00–2.87 mg/L FEU (fibrinogen-equivalent unit) and 65; 95% CI: 54–76 ×109/L, and significant risk reductions for death and thrombosis were observed; OR: 0.48; 95% CI: 0.25–0.92 and 0.35; 95% CI: 0.17–0.72.Conclusion In contrast to D-dimer levels, increase of platelet count over the first week in hospital was associated with improved survival and reduced thrombotic risk. The daily mean levels of D-dimer dropped while the platelet counts rose, coinciding with increased anticoagulation and a decline in thrombotic burden and mortality.
Keywords: COVID-19; platelet count; thrombosis; low-molecular-weight heparin